Climatological analysis of hail in the northern Zagros area during the growing season - Majid Razaee Banafsheh; Saeed Jahanbakhsh; Fatemeh Ghaderi (مخاطرات محیط طبیعی, 2018)
Agriculture is the only activity which hurts the nature the least but becomes affected by natural circumstances, especially weather. Hailstone is among the most important dangers which make agricultural activities unstable through damaging agricultural products.  Therefore, recognizing climates and studying climatological needs of agricultural plants, through fostering and utilizing human knowledge about atmospheric trends, leads to quantitative and qualitative improvement of products and subsequently stabilization of agriculture. Thus, the aim of the present research is the comprehensive study of temporal-spatial distribution and synoptic condition of these destructive phenomena For this purpose, the statistical data 23, 10 synoptic stations (2014-1992) in the growing season (April to September) with a choice of 4 cases of severe rainfalls and hail as well as data center NCEP / NCAR maps synoptic sea level 500, 850 and 1000 hPa cold wind, humidity, light, omega and frost formation in the application environment is drawn Grads. 9 to 15 (with peak rainfall at 12) Greenwich Mean Time GMT)) and the months of April, May, and June, respectively, had the highest frequency. The maximum frequency of occurrence in the region, in addition to local factors such as topography them (with altitude above sea level), the log-in system causing precipitation as west winds has an effective role. Located deep valleys caused by west winds with very cold air activities in the North, Mediterranean and Black Sea on the moisture, extreme temperature difference between the surface (due to the advection of warm, moist air at ground level) and high levels (with cold fronts) and ground-level air mass rally led by the highest frequency of hail in the spring (peak rainfall in April and May) is.